2012
DOI: 10.1111/j.1750-3841.2012.02812.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Chemical Composition or Antioxidant Activity and Antihypertensive Activity for Six Essential Oils

Abstract: Six essential oils (EOs), Juniperus phoenicea (leaves and berries), Thymus capitatus, Lauris nobilis, Melaleuca armillaris, and Eucalyptus gracilis, were screened for their antioxidant and antihypertensive activity as well as their chemical compositions. We identified and quantified 24 compounds (representing 99.8% of total oil) for J. phoenicea leaves, 14 compounds (representing 98.8% of total oil) for J. phoenicea berries, 11 compounds (representing 99.6% of total oil) for T. capitatus, 32 compounds (represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Achour et al 25 demonstrated the presence of carvacrol as main component, followed by p-cymene, c-terpinene, linalyl acetate, 1,8-cineole, b-myrcene, terpinen-4-ol and a-terpinene. Yvon et al 9 identified 11 compounds in T. capitatus oil. The main constituent is thymol, followed by p-cymene and c-terpinene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Achour et al 25 demonstrated the presence of carvacrol as main component, followed by p-cymene, c-terpinene, linalyl acetate, 1,8-cineole, b-myrcene, terpinen-4-ol and a-terpinene. Yvon et al 9 identified 11 compounds in T. capitatus oil. The main constituent is thymol, followed by p-cymene and c-terpinene.…”
Section: Discussionmentioning
confidence: 99%
“…T. satureioides and T. pallidus essential oils showed IC 50 values of 0.32 and 11.6 mg/mL, respectively, in DPPH assay 32 . The essential oil obtained from the leaves of Tunisian T. capitatus showed IC 50 values of 0.59 and 1.24 mg/L in DPPH and ABTS assay, respectively 9 . Recently, Tabti et al 31 compared the antioxidant potential of Algerian T. capitatus essential oil, ethanol extract and n-hexane extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Nayak et al 2013), Marrubium vulgare L. (Boudjelal et al 2011), Salvia hispanica L. (Munoz et al 2013) have proven to be effective, while Salvia elegans Vahl. (Jimenez et al 1988), thymus capitatus (L.) Hoffmanns & Link (Yvon et al 2012), Salvia hispanica L. (Mihailovic-Stanojevic et al 2013), and thymus serpyllum L. (Jovanovic et al 2005) can be used for hypertension.…”
Section: Medicinal Plants Of the Family Lamiaceaementioning
confidence: 99%
“…Several papers have been published on the chemical composition of the essential oil of T. capitatus (Cosentino et al, 1999;Arras and Usai, 2001;Miceli et al, 2006;El Ajjouri et al, 2008;Figueiredo et al, 2008;Blanco et al, 2010;Napoli et al, 2010;Tawaha and Hudaib, 2012;Yvon et al, 2012;BallesterCosta et al, 2013;Chedia et al, 2013;Saoud et al, 2013;Hortigo´n-Vinagre et al, 2014;Bouayad Alam et al, 2014). It is very rich in the terpenes thymol, carvacrol, and p-cymene.…”
Section: Introductionmentioning
confidence: 96%